Explaining the Party Unity of Governing Parties in Mexico - Su, Yen-Pin; Fonseca, Fabricio A. (Revista de Ciencia Política, 2021)
Previous studies have found that party unity in legislative voting tends to be higher for governing parties, but little is known about why some governing parties have higher levels of party unity than others. This study aims to fill the empirical void by conducting analyses of governing parties’ unity in legislative voting. We argue that presidential popularity matters for explaining variation in vote unity of governing parties because presidential approval is an important psychological component in executive-legislative relations. Focusing on deputies from the incumbent parties in roll-call votes for executive-sponsored bills in Mexico from 1998 through 2018, we find that the level of a governing party’s unity increases with higher presidential approval. The results are robust to a number of sensitivity tests and to controlling for potential endogeneity. <!– [if gte mso 9]> Normal 0 21 false false false ES-CL X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>